A nitrogen-doped mesoporous carbon containing an embedded network of carbon nanotubes as a highly efficient catalyst for the oxygen reduction reaction. Issue 45 (3rd November 2015) - Li, Jin-Cheng; Zhao, Shi-Yong; Hou, Peng-Xiang; Fang, Ruo-Pian; Liu, Chang; Liang, Ji; Luan, Jian; Shan, Xu-Yi; Cheng, Hui-Ming
Abstract : A Fe–N-doped mesoporous carbon embedded with a network of CNTs shows a 59 mV more positive onset potential than Pt/C. Abstract : A nitrogen-doped mesoporous carbon containing a network of carbon nanotubes (CNTs) was produced for use as a catalyst for the oxygen reduction reaction (ORR). SiO2 nanoparticles were decorated with clusters of Fe atoms to act as catalyst seeds for CNT growth, after which the material was impregnated with aniline. After polymerization of the aniline, the material was pyrolysed and the SiO2 was removed by acid treatment. The resulting carbon-based hybrid also contained some Fe from the CNT growth catalyst and was doped with N from the aniline. The Fe–N species act as active catalytic sites and the CNT network enables efficient electron transport in the material. Mesopores left by the removal of the SiO2 template provide short transport pathways and easy access to ions. As a result, the catalyst showed not only excellent ORR activity, with 59 mV more positive onset potential and 30 mV more positive half-wave potential than a Pt/C catalyst, but also much longer durability and stronger tolerance to methanol crossover than a Pt/C catalyst.